Visual Illustrations of Jinn in the Pelaga Lembu Manuscript - Shaari, Shahrul Anuar; Ab. Karim, Ab.Razak; Hamidon, Nor Azlin; Ahmad, Mohammad Nazzri (Melayu: Jurnal Antarabangsa Dunia Melayu; Vol 12 No 2 (2019): Melayu: Jurnal Antarabangsa Dunia Melayu Volume 12 Number 2 July 2019, 2019)
Illustrations of supernatural beings called jinns (genies) have long existed in the manuscripts of the Malay world. One such manuscript is Pelaga Lembu (MS1649) from Kelantan-Patani, which was composed from around the 1860s to the 1920s, and is a single manuscript describing the rites and rituals surrounding the readying of bulls for bullfighting. This manuscript contains text and illustrations of jinns, fulfilling various purposes and roles, that dominate almost every page of the manuscript. The illustrations of jinns were provided by writer-illustrators considered in the olden days to be "experts" in this field, such as shamans, mediums and medicine men, as a means to record-in visual means-the ways of handling fighting bulls. The characteristics and illustrations of jinns are interpreted, and communicated in a symbolic artistic medium through the folk art style. The image shows the variety of influences on the beliefs of the local community, with its tribal and ethnic diversity. The jinn illustrations are visual expressions displaying the belief system that lay at the very basis of the cultural practices in the Malay world some time ago. This proves that these authors were artists of their day, and that the Malay visual arts developed through writing and drawing. Keywords: Illustrations, jinn, Malay manuscripts, arts